Awareness of Tele Rehabilitation Among Physiotherapy Students of a Teaching University: A Cross-Sectional Study - Urooj Bhatti, Sikandar Ali Sangrasi, Waseem Shaikh, Sameena Gul Memon, Rubina Ahmadani, Sadia Effendi, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the awareness of tele rehabilitation among physiotherapy students of a teaching university. Study design: A cross-sectional study Place and Duration: Institute of Physiotherapy and Rehabilitation Sciences LUMHS Jamshoro from August to December 2021 Methodology: In this study data was collected from the 250 students of physiotherapy. Non probability convenience sampling technique was used to check the awareness among physiotherapy students and future possibilities of Tele rehabilitation. Data was analyzed by statistical package for the social science (SPSS) version 22. Results: In this study 250 physiotherapy students participated. Male participants were 40 (16%) and female participants were 210 (84%). A total of 192 (76.8%) students had knowledge/awareness about Tele rehabilitation and 58 (23.2%) had no knowledge. In this study female participants had more awareness (62%) as compared to male participants (22%). Conclusion: We found that majority of the study participants had a knowledge about the tele rehabilitation while female participants were more aware than male participants regarding tele rehabilitation